Meningkatkan Hasil Belajar Lempar Turbo Melalui Modifikasi Permainan Bola Berkuncir (Department of Physical Education, Sport, Health and Recreation, 2015)
Classroom Action Research was conducted with the aim to determine the improvement of learning outcomes throwing a turbo in a ball game penjasorkes through modification tasseled at Elementary School fifth grade students of Muhammadiyah 02 Bendan Pekalongan. This study uses action research. From the research conducted, an increase in student learning outcomes from the initial condition to cycle 1 (85.5%) and cycle 2 (90.5%) Students can achieve a fairly good indicator of where the meaning of learning model throwing a turbo in penjasorkes through modification tasseled ball game in the fifth grade elementary school students of Muhammadiyah 02 Bendan Pekalongan can be used